2014
DOI: 10.12659/msm.890160
|View full text |Cite
|
Sign up to set email alerts
|

ASMT gene expression correlates with cognitive impairment in patients with recurrent depressive disorder

Abstract: BackgroundRecurrent depressive disorder is a multifactorial disease; one of the typical features is cognitive impairment. The purpose of this study was analysis of ASMT gene expression both on mRNA and protein levels in patients with recurrent depressive disorder (rDD) and assessment of the relationship between plasma level of ASMT protein, gene expression on mRNA level, and cognitive performance.Material/MethodsThe study included 236 subjects: patients with rDD (n=131) and healthy subjects (n=105, CG). Cognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 52 publications
(52 reference statements)
1
11
1
Order By: Relevance
“…The possible causes of the reduction in MT level can be attributed either to the central and peripheral alterations in serotonin levels in autism that were widely reported previously 2 or to the defect in the synthesis of MT. 23 Previous studies 8 , 23 of MT production in autistic disorder were also limited by small sample sizes and were not entirely consistent, but all reported an abnormal MT production, 2 which is inconsistent with the results of the current study.…”
Section: Discussioncontrasting
confidence: 92%
“…The possible causes of the reduction in MT level can be attributed either to the central and peripheral alterations in serotonin levels in autism that were widely reported previously 2 or to the defect in the synthesis of MT. 23 Previous studies 8 , 23 of MT production in autistic disorder were also limited by small sample sizes and were not entirely consistent, but all reported an abnormal MT production, 2 which is inconsistent with the results of the current study.…”
Section: Discussioncontrasting
confidence: 92%
“…To our knowledge, there are only 2 studies in the literature that characterize mRNA expression of ASMT in the peripheral blood of recurrent DD. Galecki et al [74] and Talarowska et al [83] have demonstrated the reduced mRNA expression of ASMT in patients with depression and cognitive impairment. Surprisingly, these studies, despite promising results, have not been replicated.…”
Section: Melatonin Related-gene Expression Profile In Depressionmentioning
confidence: 99%
“…Although most studies indicate that general intelligence remains intact in patients with MS, other investigations have detected slight but significant decreases. Overt dementia is rare in MS, and the most common clinical presentation is specific and subtle cognitive deficits that can vary substantially among patients [ 3 , 13 16 ].…”
Section: Introductionmentioning
confidence: 99%